2016
DOI: 10.1200/jco.2015.64.2710
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Institutional Phase II Study of High-Dose Hypofractionated Proton Beam Therapy in Patients With Localized, Unresectable Hepatocellular Carcinoma and Intrahepatic Cholangiocarcinoma

Abstract: High-dose hypofractionated proton therapy demonstrated high LC rates for HCC and ICC safely, supporting ongoing phase III trials of radiation in HCC and ICC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
336
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 376 publications
(355 citation statements)
references
References 23 publications
(12 reference statements)
12
336
1
6
Order By: Relevance
“…Additionally, local control, particularly in extrahepatic cholangiocarcinoma, appears to be a dominant failure pattern, and associated with quality of life issues. More data that supports the role of radiation include the recently published phase II study of protons in inoperable intrahepatic cholangiocarcinoma demonstrating 2-yr local control of 95% (9). Additionally, a study by Southwest Oncology Co-operative Group (SWOG) evaluating gemcitabine plus capecitabine followed by chemoradiation demonstrated a much lower local failure than historical surgical series (10).…”
Section: Adjuvant Therapy For Cholangiocarcinoma: Different Viewsmentioning
confidence: 99%
“…Additionally, local control, particularly in extrahepatic cholangiocarcinoma, appears to be a dominant failure pattern, and associated with quality of life issues. More data that supports the role of radiation include the recently published phase II study of protons in inoperable intrahepatic cholangiocarcinoma demonstrating 2-yr local control of 95% (9). Additionally, a study by Southwest Oncology Co-operative Group (SWOG) evaluating gemcitabine plus capecitabine followed by chemoradiation demonstrated a much lower local failure than historical surgical series (10).…”
Section: Adjuvant Therapy For Cholangiocarcinoma: Different Viewsmentioning
confidence: 99%
“…The CONSORT study recently reported the results of 92 patients with unresectable HCC or IHCC treated with moderately hypofractionated proton therapy (37). Of note, the tumor size in this study was much larger than previous trials with a median size of approximately 6 cm (median gross tumor volume of 133.7 cc).…”
Section: Moderately Hypofractionated Proton Therapymentioning
confidence: 66%
“…Regarding HCC, in addition to the multiple studies reporting no grade ≥3 toxicities, support from prospective phase II data (35,40) and a phase III trial (41) demonstrating numerical superiority of PBT have provided high-quality evidence that PBT is, at minimum, equivalent to existing standards of care. In this phase III trial, the decreased post-therapy hospitalization rate provides a pertinent endpoint for which PBT was clearly superior to TACE; these results have major implications for cost-effectiveness (77).…”
Section: Discussionmentioning
confidence: 99%
“…This report mirrors other studies demonstrating no grade ≥3 toxicities, presented in Table 3 (32,36,37). The results of a prospective phase II trial of PBT in 83 patients with unresectable HCC (n=44), intrahepatic cholangiocarcinoma (n=37), or mixed (n=2) have recently been reported (40). The vast majority (80%) of patients had Child-Pugh grade A disease, and prior treatment (most frequently, chemotherapy) had been administered to 32% of HCC and 62% of cholangiocarcinoma patients.…”
Section: Livermentioning
confidence: 99%